1991
DOI: 10.1111/j.2044-8309.1991.tb00950.x
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent health behaviour and similarity‐attraction: Friends share smoking habits (really), but much else besides

Abstract: Smoking habits and related attitudes were assessed in a sample of 4059 11- to 16-year-olds who also identified their best friends from among their fellow respondents. Subjects' responses were directly collated with those of their friends and indicated a clear covariation of smoking status (controlling for sex and age) as anticipated from previous research in which adolescents have been asked to report on the smoking habits of their friends. Such covariation, however, was not specific to smoking habits, but gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
63
0
2

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(69 citation statements)
references
References 8 publications
4
63
0
2
Order By: Relevance
“…Our results also showed that adolescent friends share similar sun exposure and sun protective behaviours as well as similar parenting backgrounds. These findings are in in accordance with other research showing that adolescent friends share similar behaviours across a wide range of variables some of which are relevant to health (e.g., Eiser et al, 1991;Mercken et al, 2009). However, to our knowledge these relationships have not previously been demonstrated with regard to adolescents' sun exposure and sun protection behaviours.…”
Section: A J Mewse Et Al 18supporting
confidence: 81%
See 2 more Smart Citations
“…Our results also showed that adolescent friends share similar sun exposure and sun protective behaviours as well as similar parenting backgrounds. These findings are in in accordance with other research showing that adolescent friends share similar behaviours across a wide range of variables some of which are relevant to health (e.g., Eiser et al, 1991;Mercken et al, 2009). However, to our knowledge these relationships have not previously been demonstrated with regard to adolescents' sun exposure and sun protection behaviours.…”
Section: A J Mewse Et Al 18supporting
confidence: 81%
“…Previous research has consistently shown that adolescent friends show similarities across a wide range of behaviours (Cohen, 1977;Eiser, et al, 1991), some of which are relevant to health (e.g., Mercken, Candel, Willems, & de Vries, 2009). These similarities have most commonly been viewed as a consequence of peer influence.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The results of one American study (Vicary, Smith & Caldwell et al, 1998) which found that increases in social activities such as parties, dating, being with a crowd (and for females only, decreases in sports, hobbies and crafts and church involvement) most often occurred prior to increased alcohol use, suggest that the additional time spent hanging out with peers provides the incentive or opportunity for increased alcohol use rather than the other way around. These results should be contrasted with those which suggest that to some extent young people select their friends on the basis of characteristics such as smoking (Ennett & Baumann, 1994;West, Sweeting & Ecob, 1999) and the more general view that children and young people choose, at least partly, the influences they experience (Hill, 1990;Eiser, Morgan & Gammage et al, 1991).…”
Section: Discussionmentioning
confidence: 39%
“…Adolescents who smoke are more likely to have smoker friends than non-smoking adolescents, suggesting that individuals may initiate smoking to conform and gain peer approval (Eiser, Morgan, Gammage, Brooks, & Kirby, 1991;Webster, Hunter, & Keats, 1994). A third source of social influence in young adult tobacco use is the media.…”
Section: Role Models and Young Adults' Smoking Behaviorsmentioning
confidence: 99%